Photocatalytic degradation of sulfamethazine in aqueous solution using ZnO with different morphologies - Zhigang Yi (Royal Society Open Science, 2018)
In this study, photocatalytic experiments of 20 mg l−1 sulfamethazine (SMN) in aqueous solution containing ZnO with different morphologies, tetra-needle-like ZnO (T-ZnO), flower-like ZnO (F-ZnO) and nanoparticles ZnO (P-ZnO), were performed. The results indicated that photocatalytic degradation of SMN was effective and followed the pseudo-first-order reaction, but the degree of SMN mineralization showed obvious differences using ZnO with different shapes. After 12 h irradiation, 86%, 71% and 50% of the initial total organic carbon was eliminated in SMN suspension containing T-ZnO, F-ZnO and P-ZnO, respectively. The release ratio of sulfur was close to 100% in the presence of T-ZnO, but reached to 86% and 67% in the presence of F-ZnO and P-ZnO, respectively. The release ratio of nitrogen was about 76%, 63% and 40% using T-ZnO, F-ZnO and P-ZnO as photocatalyst, respectively. The morphology of ZnO played an important role in determining its catalytic activity. Seven intermediates were observed and identified in the UV/T-ZnO reaction system by LC-MS/MS analysis, and a possible degradation pathway was proposed.